Photoexcitation and oxygen ordering in YBa2Cu3Ox films - Osquiguil, E.; Maenhoudt, M.; Wuyts, B.; Bruynseraede, Y.; Lederman, D.; Schuller, I.K. (American Physical Society, 1994)
Fil: Osquiguil, E. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Katholieke Univetsiteit Leuve; Bélgica